2022
DOI: 10.1038/s41467-022-30467-5
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate proteoglycans prevent immune cell phenotypic conversion and inflammation resolution via TLR4 in rodent models of spinal cord injury

Abstract: Chondroitin sulfate proteoglycans (CSPGs) act as potent inhibitors of axonal growth and neuroplasticity after spinal cord injury (SCI). Here we reveal that CSPGs also play a critical role in preventing inflammation resolution by blocking the conversion of pro-inflammatory immune cells to a pro-repair phenotype in rodent models of SCI. We demonstrate that enzymatic digestion of CSPG glycosaminoglycans enhances immune cell clearance and reduces pro-inflammatory protein and gene expression profiles at key resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 93 publications
0
37
0
Order By: Relevance
“…Fibrous scar formation is considered to be a major factor in limiting axon regeneration in the adult mammalian CNS ( 2 ). Several scar components, such as myelin-associated factors, basal lamina components, and high molecular weight chondroitin sulfate proteoglycans (CSPGs), have been identified as inhibitors of axonal regrowth through mechanisms including growth cone collapse, repellence or entrapment, and prevention of inflammation resolution ( 35 ). However, removing these extracellular matrix (ECM) factors results in only modest regeneration, suggesting that critical molecules and mechanisms contributing to regeneration failure remain to be discovered ( 68 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous scar formation is considered to be a major factor in limiting axon regeneration in the adult mammalian CNS ( 2 ). Several scar components, such as myelin-associated factors, basal lamina components, and high molecular weight chondroitin sulfate proteoglycans (CSPGs), have been identified as inhibitors of axonal regrowth through mechanisms including growth cone collapse, repellence or entrapment, and prevention of inflammation resolution ( 35 ). However, removing these extracellular matrix (ECM) factors results in only modest regeneration, suggesting that critical molecules and mechanisms contributing to regeneration failure remain to be discovered ( 68 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is new evidence showing that they can regulate multiple aspects of the immune response in chronic inflammatory and demyelinating disorders of the CNS. In a new study by Francos-Quijorna et al (2022) , the molecular and cellular basis of these immunomodulatory effects of CSPGs were investigated. They showed that CSPGs impede the resolving phase of wound repair and that this results in the wound remaining in a chronic state.…”
Section: The Glial Scar: Its Impact and Cellular Players Involvedmentioning
confidence: 99%
“…It also promotes wound resolution by digesting CSPGs. This results in a bias of microglial phenotype from M1-like pro-inflammatory type to favor the M2-like phenotype which promotes wound healing ( Francos-Quijorna et al, 2022 ). Furthermore, axon outgrowth is further enhanced by targeting ChABC to the axonal compartment ( Day et al, 2020 ).…”
Section: The Quest For Axonal Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In many contexts, the inflamed CNS experiences an ingress of bone marrow-derived monocytes, which differentiate into monocyte-derived macrophages and play a pleiotropic role in neuroinflammation [ 58 ]. Macrophage interactions with myelin debris and chondroitin sulfate proteoglycans in the glial scar induce the production of pro-inflammatory cytokines and reactive species that propagate neurotoxic inflammation [ 59 , 60 ]. Conversely, the presence of bone marrow-derived macrophages also mitigates microglial reactivity and ultimately reduces inflammation after CNS injury [ 61 , 62 ].…”
Section: Effectors Stimuli and Outcomes Of Neuroinflammationmentioning
confidence: 99%